Petrologia do plúton granitico serra verde, porção lestre do domínio seridó - Costa, Lindaray Sousa da (2009)
The study area is located at the eastern-central portion of the Seridó Belt, on the interface between the Seridó Group Metasediments and the crystalline basement rocks of the Caicó Complex (RN). Petrographic and geochemical data allow us to define aspects related to the genesis and evolution of the Serra Verde Pluton magmas, which composes the goal of this dissertation The Serra Verde Pluton is a stock with outcropping area of about 25 km², which is intrusive into metasedimentary sequence and the basement gneisses. The pluton intrusion is sintectonic to the Brasiliano event, elongated along the NE direction, developing a cornue geometry. The rock is a monzogranite mainly composed by K-feldspar, plagioclase and quartz, which usually compose more than 85% of the modal analisys. The main mafic mineral is the biotite, while amphibole, sphene, epidote, opaque minerals, allanite, zircon and apatite occur as accessory minerals. It features still a latemagmatic paragenesis composed by chlorite, granular epidote, carbonates and muscovite, developed through the percolation of late CO2 and H2O rich fluids. Chemically, the Serra Verde Pluton rocks may be classified as metaluminous, of calc-alkaline affiliation, sometimes showing trondhjemític characteristics, with high Na2O (>4,5%), Sr (>400ppm) and Ba (>800ppm) and low K2O (≤3,0%), MgO (<1,0%), TiO2 (<0,5%), Rb (<90ppm), Y (≤16ppm) and Zr (≤13ppm). Micropetrographic evidences (mineral assembly and microtextures) indicate that the magma evolution occurred in moderated to high fO2 conditions, above the FMQ buffer. Thermo-barometric data obtained by minor elements geochemistry and the CIPW data, suggest a final/minimal pressure crystallization for the Serra Verde Pluton samples of about 3 to 5 kbar, liquidus temperature around 800o C, solidus temperature between 680o and 660o C. This data is compatible with those observed by many authors for the Neoproterozoic granites of the Seridó Belt. The group of analyzed data (Petrographic, microtextural and geochemical), suggests that the dominant process of the generation and evolution of the Serra Verde Granite magma was the fractional crystallization, probably from basement quartz-dioritic and tonalitic orthogneisses source